A statistical model of aggregate fragmentation - Spahn, F.; Vieira Neto, E. [UNESP]; Guimaraes, A. H. F. [UNESP]; Gorban, A. N.; Brilliantov, N. V. (Iop Publishing Ltd, 2014)
A statistical model of fragmentation of aggregates is proposed, based on the stochastic propagation of cracks through the body. The propagation rules are formulated on a lattice and mimic two important features of the process-a crack moves against the stress gradient while dissipating energy during its growth. We perform numerical simulations of the model for two-dimensional lattice and reveal that the mass distribution for small-and intermediate-size fragments obeys a power law, F(m) proportional to m(-3/2), in agreement with experimental observations. We develop an analytical theory which explains the detected power law and demonstrate that the overall fragment mass distribution in our model agrees qualitatively with that one observed in experiments.